Synergistic effects of EU Taxonomy and BREEAM for new construction buildings in Iceland - Nína María Hauksdóttir 1995- (2024)
With buildings accounting for 40% of greenhouse gas emissions worldwide, it is crucial to mitigate their impact. Sustainable buildings provide a range of advantages such as decreased environmental impact, energy efficiency, enhanced occupant well-being, long-term financial savings, and increased resilience to climate change. The BREEAM certification scheme has long been utilized in this regard, and as of 12th of July 2020, the EU Taxonomy regulation (EU 2020/852) has come into effect in the EU and was implemented in Iceland from 1st of June 2023. Thesis explores the synergy between BREEAM certification and the EU Taxonomy framework for new construction buildings in Iceland. It evaluates how buildings in Iceland align with EU Taxonomy after obtaining a BREEAM certification. The research highlights that BREEAM and EU Taxonomy have similar criteria, and concludes that buildings can potentially meet most EU Taxonomy criteria with minimal additional effort if the EU Taxonomy criteria is considerate early in the BREEAM certification process. However, full EU Taxonomy alignment is currently unachievable in Iceland due to legislative gaps, specifically the non-implementation of Directive 2010/31/EU, which affects energy performance certifications for buildings. Byggingar bera ábyrgð á 40% af losun gróðurhúsalofttegunda um allan heim og því er mikilvægt að draga úr áhrifum þeirra. Sjálfbærar byggingar veita margvíslega kosti eins og minni umhverfisáhrif, betri orkunýtingu, aukna vellíðan notenda, langtíma fjárhagslegan sparnað og aukið þol gegn loftslagsbreytingum. BREEAM vottunarkerfið hefur lengi verið notað í þessu sambandi og frá og með 12. júlí 2020 tók EU Taxonomy flokkunarreglugerð ESB (ESB 2020/852) gildi og var innleidd á Íslandi 1. júní 2023. Ritgerðin fjallar um samlegðaráhrif BREEAM vottunar og EU Taxonomy flokkunarreglugerðarinnar fyrir nýbyggingar á Íslandi. Hún metur einnig hvernig byggingar á Íslandi samræmast EU Taxonomy flokkunarkerfinu eftir að hafa hlotið BREEAM vottun. Rannsóknin leiðir í ljós að ...